Molecular and Biological Characterization of the First Hypovirus Identified in Fusarium oxysporum - Torres-Trenas, Almudena; Cañizares, M. Carmen; García-Pedrajas, M. Dolores; Pérez-Artés, Encarnación (Frontiers in Microbiology, 2020)
A novel mycovirus named Fusarium oxysporum f. sp. dianthi hypovirus 2 (FodHV2) has been identified infecting isolates Fod 408 and Fod 409 of Fusarium oxysporum f. sp. dianthi from Morocco. The genome of FodHV2 is 9,444 nucleotides long excluding the poly(A) tail, and has a single open reading frame (ORF) encoding a polyprotein. The polyprotein contains three highly conserved domains of UDP glucose/sterol glucosyltransferase, RNA-dependent RNA polymerase, and viral RNA helicase. In addition, particular residues of Cys, Hys, and Gly detected in the N-terminal region suggest the presence of the catalytic site of a highly diverged papain-like protease. Genomic organization, presence of particular conserved motifs, and phylogenetic analyses based on multiple alignments clearly grouped FodHV2 with the members of the family Hypoviridae. FodHV2 was transferred by hyphal anastomosis to a recipient HygR-tagged virus-free strain. The comparison of the infected and non-infected isogenic strains showed that FodHV2 did not alter the vegetative growth, neither the conidiation nor the virulence of its fungal host. Efficiency of FodHV2 transmission through the conidia was 100% in both the original and the recipient infected-isolates. To the best of our knowledge, this is the first report of a hypovirus infecting the plant pathogen F. oxysporum, and also the first one of a hypovirus detected in a fungal strain from the African continent.